Informality, Frictions, and Macroprudential Policy - Ben Hassine, Moez (IMF Working Papers; Working Paper, 2019)
We analyze the effects of macroprudential policies through the lens of an estimated dynamic stochastic general equilibrium (DSGE) model tailored to developing markets. In particular, we explicitly introduce informality in the labor and goods markets within a small open economy embedding financial frictions, nominal and real rigidities, labor search and matching, and an explicit banking sector. We use the estimated version of the model to run welfare analysis under optimized monetary and macroprudential rules. Results show that although informality reduces the efficiency of macroprudential policies following a convex fashion, combining the latter with an inflation targeting objective could be beneficial.